The effects of RU486, used as a postcoital contraceptive, on the rat uterus during early pregnancy - Theron, Kathrine Elizabeth (My University, 2011)
Tissue specific regulation of the progesterone receptor is central to female health. The synthetic steroid, RU486 is a partial progesterone and oestrogen receptor antagonist, functioning to actively silence progesterone receptor gene associated transcription. For this reason, it has been used both as a contraceptive and quite controversially as an abortive agent. In this study, both cellular and gene specific effects of RU486 were investigated in a rat model of early pregnancy, this including the key phases of the plasma membrane transformation, the window of receptivity and early implantation. As all of these stages are hormonally regulated by progesterone and oestrogen, the focus here was to elucidate the mechanisms of action of a single dose of RU486, used as a postcoital contraceptive, at day 3.0 of pregnancy, to successfully prevent implantation of a viable blastocyst and subsequent pregnancy. In association with the cellular preparation of uterine epithelial cells for implantation, selected molecular targets and events were investigated at a protein and gene expression level, both prior to and after RU486 treatment, to assess the effects of either a deficit or excessive expression of these gene products on uterine preparation and eventual implantation. Factors here included the progesterone receptor, markers of apoptosis (Bax and Bcl2), mediators of angiogenesis (VEGF, bFGF and PDGF) and biomarkers of endometrial implantation (LIF, Calcitonin and Muc-1). Together, an ultrastructural and light microscopy analysis showed RU486 to morphologically alter the uterine endometrial cells and to disrupt the plasma membrane transformation of early pregnancy, predisposing these cells towards apoptosis. In association with this, progesterone receptor gene and protein expression was ubiquitously decreased throughout pregnancy. With regards to the implantation process of early pregnancy, the luminal epithelial cells undergo apoptosis to allow the hatching blastocyst to penetrate and implant within the uterine wall. This is partially mediated by the ratio of the expression of the apoptotic factors Bax and Bcl-2. Surprisingly here, RU486 caused an overall anti-apoptotic environment, despite previously observed high levels of apoptotic activity. This indicates that factors other than Bax and Bcl-2 influence the RU486-induced apoptosis. A crucial event of early pregnancy is the establishment of an adequate blood supply to sustain and nourish the implanting blastocyst. There was a decided reduction in the angiogenic response of early pregnancy, as a direct consequence of RU486 treatment; the normally high levels of VEGF and bFGF during early pregnancy, were markedly decreased at all three days of pregnancy. This was reflected in the lack of increased vascularisation as normally signalled by the indicator dye, Pontamine Sky blue. In contrast to the overall increase in VEGF and bFGF at the time of blastocyst implantation during early pregnancy, increased PDGF expression was localised to the implantation sites, strongly suggesting a role for this angiogenic factor in endothelial cell proliferation. v The endometrial biomarkers are indicative of implantation, their expression patterns varying around the phase of implantation. These markers are essential to implantation, as when LIF and Calcitonin are deregulated and Muc-1 persists on the apical surface of the endometrium, implantation fails. These events are precisely what occur following RU486 treatment. In summary, the overall effects of RU486 in the rat model of early pregnancy, when used as a postcoital contraceptive, indicate highly effective inhibition of progesterone and oestrogen effects on the endometrium, mediated by their receptors. More specifically, the structural and molecular events mirror those described in ovariectomised animal models, suggesting a hormonally under-stimulated endometrium. Clearly from the present study, the precise priming of the endometrium in preparation for blastocyst implantation is severely impaired by RU486 through a number of signalling pathways, thus predisposing the uterus to pregnancy failure.
PhD,School of Anatomical Sciences, Faculty of Health Sciences, University of the Witwatersrand
Keywords: RU486; steroids; synthetic hormones; postcoital contraceptive